DEVIANT BEHAVIOR OF ADOLESCENTS AND SOCIO-PEDAGOGICAL CONDITIONS FOR ITS CORRECTION - Taylakova, Sh. (SCIENCE and SOCIETY, 2023)
Socialization is a continuous process, that is, a person constantly interacts with society. Education is a continuous process. Because it is implemented in certain organizations and is limited in time and space. In particular, there are a number of socio-pedagogical factors for the prevention of negative behavior in the upbringing of minors, each of these factors has its own characteristics in the educational process. The article deals with the socio-pedagogical factors in the prevention of negative moral forms of adolescent behavior.